Some inlays, a stone mace and an engraved plaque: Elements for a short note on Kish iconography of war - Couturaud, Barbara (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Although Kish is seen today as one of the most prestigious Mesopotamian cities of the 3rd millennium, the iconographic evidence that has been found there is, nevertheless, quite limited, especially images related to war. The best-known of these are the fragments of inlays representing military scenes featuring soldiers and prisoners. More recently, a plaque of unknown origin has been interpreted as coming from Kish. This paper, in the form of a short note, is an opportunity to publish a stone mace found at Mari, but which certainly originated from Kish, and to reconsider the few known objects bearing an iconography related to war and most probably belonging to Kish. While it is obvious that much data, especially related to the archaeological contexts of the objects, is missing, we hope that these few reflections will contribute to a broader discussion on the iconographic identity of the Mesopotamian city-states during the Early Bronze Age.